What's in a 510(k)? [medical device marketing]. - Munzner, R.
If you hope to market a new medical device in the United States, sending a premarket notification, or 510(k) is probably the easiest and fastest way to do so. The article briefly looks at the 510(k) and outlines what it is, gives guidelines for preparing it including useful resources, and gives an idea of fees and review time required.